1980
DOI: 10.1111/j.1442-9071.1980.tb00340.x
|View full text |Cite
|
Sign up to set email alerts
|

Macular Oedema and Retinal Branch Vein Occlusion

Abstract: SummaryRetinal branch vein occlusion is a common cause of retinal vascular disease and because macular oedema is a frequent complication, prognostic factors in these cases have been closely studied?From these investigations, suggested factors with prognostic signficance have been the site of occlusion, extent of the macular oedema and disruption of the foveal arcade.The retinal vasculature has been described as responding in two ways to venous occlusion.' The blood vessels may become dilated and leak as a resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 1 publication
0
12
0
Order By: Relevance
“…Visual loss in BRVO is either caused by local ischemia, intraretinal hemorrhages, or macular edema. The latter is the most common cause of long-standing poor visual outcome secondary to BRVO [3]. So far, laser photocoagulation is the gold standard of treatment in cases with BRVO, following the recommendations of the Branch Vein Occlusion Study (BVO) [1], the only randomized long-term evaluation of any therapy in this retinal vascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Visual loss in BRVO is either caused by local ischemia, intraretinal hemorrhages, or macular edema. The latter is the most common cause of long-standing poor visual outcome secondary to BRVO [3]. So far, laser photocoagulation is the gold standard of treatment in cases with BRVO, following the recommendations of the Branch Vein Occlusion Study (BVO) [1], the only randomized long-term evaluation of any therapy in this retinal vascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Macular oedema is the major cause of visual disturbance in BRVO, occurring in about 60% of cases. 10 The degree of macular involvement determines the level of visual impairment. At present, macular grid laser photocoagulation has been the only established treatment modality for macular oedema arising from BRVO, but the visual acuity improvement is often very limited (average improvement in vision of 1.33 Snellen lines).…”
Section: Introductionmentioning
confidence: 99%
“…ME is a main cause of severe visual impairment after BRVO, which is a common vascular retinal disease [1,2]. The BRVO study demonstrated that laser-treated eyes on average gained 1.33 lines at 3 years after grid laser treatment [4].…”
Section: Discussionmentioning
confidence: 99%
“…In the age group over 49 years, the cumulative incidence of BRVO is about 1.2% in 10 years [1]. Macular edema (ME) is the most frequent complication of BRVO (60%) and a major cause of visual loss in BRVO patients [2]. Vision can also be diminished by ischemia and vitreous hemorrhage from neovascularization.…”
Section: Introductionmentioning
confidence: 99%